Analisis Penjadwalan Proses Produksi Billboard dengan Metode CPM (Critical Path Method) : Studi Kasus Pada Cv. Total Agra Mandiri di Kota Bandung - Gloria Wesuranaita; Resi Juariah Susanto (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This study analyzes the scheduling of billboard production processes at CV. Total Agra Mandiri in Bandung using the Critical Path Method (CPM) to identify production activities, determine critical paths, and compare production completion times. The research employed a qualitative method with a descriptive approach through interviews, documentation, and literature studies to obtain comprehensive data related to production scheduling. The findings indicate that the production completion time before the implementation of CPM was 27 days. After applying CPM, the production duration was successfully reduced to 25 days, demonstrating improved efficiency in production planning. The analysis also revealed that all production activities were included in the critical path with zero slack time, meaning that any delay in these activities would directly affect the overall production schedule. The identified critical paths were A–B–C–D–F–G–H–I–J–K and A–B–C–E–F–G–H–I–J–K. Therefore, these activities require strict monitoring and optimal control to prevent production delays and ensure timely completion of billboard production processes.